2006
DOI: 10.1021/jp062381u
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of the Cation Motion upon Adsorption of CO2 in Faujasite Zeolite Systems

Abstract: Molecular Dynamics simulations have been carried out in NaX and NaY Faujasite systems to deepen understanding of the cation rearrangement during the CO2 adsorption process suggested by our recent diffusivity measurements. This study is a major contribution since the rearrangement of the cations in Faujasite, the most promising adsorbent for CO2 storage, can represent a significant breakthrough in understanding the adsorption and diffusion processes at the mircroscopic scale. For NaY, it has been shown that at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 35 publications
8
58
2
Order By: Relevance
“…This is supported by our recent GCMC simulations (Maurin et al accepted) which revealed for LiY a higher enthalpy of CO 2 adsorption at low coverage due to an average Li + (SII)-O(CO 2 ) distance (2.10 Å) shorter than the Na + (SII) analogue (2.50 Å). However, our MD simulations show that beyond the initialisation of the diffusion, there is also a concerted (Li + -CO 2 ) motion similar to those previously pointed for Na + (Plant et al 2006) which induces a redistribution of the cations within the supercage. An illustration of the rearrangement of Li + upon CO 2 diffusion is provided in Fig.…”
Section: Resultssupporting
confidence: 82%
“…This is supported by our recent GCMC simulations (Maurin et al accepted) which revealed for LiY a higher enthalpy of CO 2 adsorption at low coverage due to an average Li + (SII)-O(CO 2 ) distance (2.10 Å) shorter than the Na + (SII) analogue (2.50 Å). However, our MD simulations show that beyond the initialisation of the diffusion, there is also a concerted (Li + -CO 2 ) motion similar to those previously pointed for Na + (Plant et al 2006) which induces a redistribution of the cations within the supercage. An illustration of the rearrangement of Li + upon CO 2 diffusion is provided in Fig.…”
Section: Resultssupporting
confidence: 82%
“…Besides other experimental conditions (such as pressure, temperature, and moisture), the topology, and composition of the zeolite govern the forces involved in the adsorption process and the overall adsorption efficiency. For instance, at low pressure the amount of CO 2 adsorbed appears to be highly influenced by the nature and density of the cations inside the zeolite pores, [4][5] whereas the pore shape and volume appear to control the adsorption capacity at high pressures. 6 Molecular simulation is a powerful tool to accurately predict adsorption and diffusion processes in crystalline porous materials, 7 and has been extensively used for predicting the adsorption of carbon dioxide in zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding CO 2 adsorption and separation, it is of great significance to obtain high CO 2 adsorption capacity because the CO 2 adsorption behavior greatly influences the CO 2 separation and desorption processes on NaY particle and membrane. A number of efforts have been made to address CO 2 adsorption behavior via different adsorbents and techniques (Lee et al 2002;Harlick and Tezel 2004;Li and Tezel 2007;Siriwardane et al 2003;Jaramillo and Chandross 2004;Khelifa et al 2004;Li et al 2000Li et al , 2008Walton et al 2006;Maurin et al 2005;Gao et al 2004;Kusakabe et al 1997, Plant et al 2006Sebastian et al 2007;Chou and Chen 2004;Othman et al 2006;Zheng and Gu 1998). Yong et al (2002) reviewed the adsorption of CO 2 on different adsorbents at relatively high temperatures.…”
Section: Introductionmentioning
confidence: 99%